Autocrine signaling via release of ATP and activation of P2X7 receptor influences motile activity of human lung cancer cells - Takai, Erina (Springer Netherlands, 2014)
Extracellular nucleotides, such as ATP, are released from cells and play roles in various physiological and pathological processes through activation of P2 receptors. Here, we show that autocrine signaling through release of ATP and activation of P2X7 receptor influences migration of human lung cancer cells. Release of ATP was induced by stimulation with TGF-β1, which is a potent inducer of cell migration, in human lung cancer H292 cells, but not in noncancerous BEAS-2B cells. Treatment of H292 cells with a specific antagonist of P2X7 receptor resulted in suppression of TGF-β1-induced migration. PC-9 human lung cancer cells released a large amount of ATP under standard cell culture conditions, and P2X7 receptor-dependent dye uptake was observed even in the absence of exogenous ligand, suggesting constitutive activation of P2X7 receptor in this cell line. PC-9 cells showed high motile activity, which was inhibited by treatment with ecto-nucleotidase and P2X7 receptor antagonists, whereas a P2X7 receptor agonist enhanced migration. PC-9 cells also harbor a constitutively active mutation in epidermal growth factor receptor (EGFR). Treatment with EGFR tyrosine kinase inhibitor AG1478 suppressed both cell migration and P2X7 receptor expression in PC-9 cells. Compared to control PC-9 cells, cells treated with P2X7 antagonist exhibited broadened lamellipodia around the cell periphery, while AG1478-treated cells lacked lamellipodia. These results indicate that P2X7-mediated signaling and EGFR signaling may regulate migration of PC-9 cells through distinct mechanisms. We propose that autocrine ATP-P2X7 signaling is involved in migration of human lung cancer cells through regulation of actin cytoskeleton rearrangement. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11302-014-9411-x) contains supplementary material, which is available to authorized users.